A Morphological Analysis of Word Formation Processes in CNN News Selected Articles - Nursa Afdila; Yusriati Yusriati (Jurnal Pendidikan Indonesia, 2026)
This research conducts a morphological analysis of word formation processes found in selected CNN News entertainment articles. The study aims to identify and categorize the types of word formation processes, analyze their occurrences, and determine the most dominant process used in five selected articles from the entertainment section of CNN News. This research employed a qualitative research design, and the data were analyzed using the theory of word formation proposed by George Yule (2020). The scope of the study was limited to five CNN News entertainment articles published between January and March 2025. The data consisted of words found in the selected news articles from the CNN News entertainment section. Data collection and analysis were carried out systematically following the procedures suggested by Miles and Huberman (1994). The findings revealed seven types of word formation processes in the selected articles: 52 borrowings, 96 compoundings, 12 clippings, 15 conversions, 21 coinages, 248 derivations, and 58 multiple processes. These processes occurred through borrowing words from other languages, combining two words into a single form, shortening existing words, changing word classes, creating words from well-known names or brands, adding affixes, and applying more than one word formation process simultaneously. Furthermore, the results showed that derivation was the most dominant word formation process among all categories identified in the selected articles.